Iconografía tiwanaku en la parafernalia inhalatoria de los Andes centro-sur - Torres, Constantino M. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2001)
En este trabajo se presenta un análisis de la iconografía tiwanaku en los equipos de inhalar polvos psicoactivos, con referencia a la escultura lítica, textiles y cerámica. Estos equipos permiten un estudio inicial de la configuración iconográfica tiwanaku debido a su función específica y a su amplia distribución geográfica y temporal. El ajuar inhalatorio consiste de una tableta rectangular, un tubo, una cucharilla y una bolsa de cuero como recipiente para los polvos. El autor ha documentado 84 tabletas y 23 tubos con este tipo de iconografía. Se discuten los temas representados, sus variaciones y componentes, y distribución geográfica.

Tiwanaku Iconography in South Central Andean Snuffing ParaphernaliaThis work presents an analysis of Tiwanaku iconography depicted on snuffing equipment, referring to other media when appropriate. This hallucinogenic equipment facilitates a basic study of Tiwanaku's iconographic configuration because of its specific function, duration and widespread distribution. The snuffing kit consists of a distinct set of implements: a small rectangular tray, a snuffing tube, a small spoon, and leather pouches that functioned as snuff powder containers. I have documented 84 snuff trays and 23 snuffing tubes with Tiwanaku iconography. Their geographical distribution is noted and the major themes represented are discussed. This is followed by an analysis of the components of the iconographic system, a discussion of the different structural schemes and variations in thematic emphasis.
Keywords: Arqueología; Tiwanaku; Iconografía; Alucinógenos; Equipo de Inhalación; Distribución Geográfica; Archaeology; Tiwanaku; Iconography; Hallucinogenic; Snuffing Equipment; Geographical Distribution; https://purl.org/pe-repo/ocde/ford#6.01.02